The Impact of Communications Methods on Team’s Productivity and Performance - Oil and Gas case study - Gaghman, Abdulghani (Technium Social Sciences Journal, 2021)
The development of multidisciplinary team communication in oil and Gas industry is a complex area that increasingly impact on team performance and achieve the common goals. Communication is the exchange of information through actions, speech and writing or symbols. Effective team communication increases; team member’s effectiveness and satisfaction because they are given the appropriate guidelines, tools and direction on how to accomplish tasks. Team members communicate via meeting, phone calls and emails. However, In the latest year’s communication tool has increased significantly as the business world has gone global and more virtual communication options are introduced, (i.e. Skype, WebEx and Smartphones). The aim of this paper was to assess the team communication process and quantity the issues, in order to avoid project delays and suboptimal performance. To determine the extent to which verbal communication approach has an impact among the organization behavior and on the integration, effectiveness and efficiency of the team. This paper had examined this subject in one of the national Oil and Gas company, and concluded that team productivity and performance are highly affected by the way of the communication and the best way is to have effective face-to-face meeting with clear objective in regular basis.